2005
DOI: 10.1128/jvi.79.18.12095-12099.2005
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Human Cytomegalovirus-Encoded MicroRNAs

Abstract: MicroRNAs (miRNAs) are an extensive class of noncoding genes that regulate gene expression through posttranscriptional repression. Given the potential for large viral genomes to encode these transcripts, we examined the human cytomegalovirus AD169 genome for miRNAs using a bioinformatics approach. We identified 406 potential stem-loops, of which 110 were conserved between chimpanzee cytomegalovirus and several strains of human cytomegalovirus. Of these conserved stem-loops, 13 exhibited a significant score usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
223
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 254 publications
(240 citation statements)
references
References 11 publications
11
223
0
3
Order By: Relevance
“…This analysis led to the identification of 13 candidate miRNA sequences encoded throughout the viral genome. Expression of five of the 13 miRNAs, miR-UL36-1, miR-UL70-1, miR-US4-1, miR-US5-1 and miR-US5-2, was confirmed through northern blot analysis (Grey et al, 2005). Following this study, and those of two other groups, a total of 11 miRNAs have been identified, including miR-UL22A-1, miR-UL112-1, miR-UL148D-1, miR-US25-1, US25-2, US33-1 and the five previously described (Dunn et al, 2005;Pfeffer et al, 2005).…”
Section: Identification Of Hcmv Encoded Mirnasmentioning
confidence: 93%
See 1 more Smart Citation
“…This analysis led to the identification of 13 candidate miRNA sequences encoded throughout the viral genome. Expression of five of the 13 miRNAs, miR-UL36-1, miR-UL70-1, miR-US4-1, miR-US5-1 and miR-US5-2, was confirmed through northern blot analysis (Grey et al, 2005). Following this study, and those of two other groups, a total of 11 miRNAs have been identified, including miR-UL22A-1, miR-UL112-1, miR-UL148D-1, miR-US25-1, US25-2, US33-1 and the five previously described (Dunn et al, 2005;Pfeffer et al, 2005).…”
Section: Identification Of Hcmv Encoded Mirnasmentioning
confidence: 93%
“…It is now thought that regulation of gene expression by miRNAs is a mechanism common to all metazoan organisms (Bartel, 2004;Pfeffer et al, 2005;Pfeffer et al, 2004). In addition, a number of studies by multiple groups have clearly shown that mammalian DNA viruses, especially of the herpesvirus family, have evolved their own miRNA genes (Burnside et al, 2006;Cai et al, 2005;Cai et al, 2006;Cui et al, 2006;Dunn et al, 2005;Grey et al, 2005;Gupta et al, 2006;Lu and Cullen, 2004;Pfeffer et al, 2005;Pfeffer et al, 2004;Samols et al, 2005;Sano et al, 2006;Sullivan et al, 2005;Yao et al, 2007). In this review, the identification and characterization of miRNAs expressed by human cytomegalovirus, and the genes they target, will be discussed.…”
mentioning
confidence: 97%
“…This tissue specificity suggests that CMV may activate multiple transcriptional programs depending on the The mechanisms underlying tissue specificity of viral gene expression may also relate to recently described and generally conserved microRNAs (miRNAs) of CMV (77)(78)(79)(80)(81). These small, noncoding RNA species have diverse effects including regulation of viral replication and immune evasion, which appear to vary by the cell type infected (77)(78)(79)(80)(81)(82)(83). HCMV-miR-UL112-3p, for example, appears to affect both the stress-induced ligand MICB and the antiviral interferon-response element IRF-1 (80,84).…”
Section: Viral Genetics and Variability In Immune Responsementioning
confidence: 96%
“…Lecellier et al (2005) found that a cellular miRNA, miR-32, mediated antiviral defense in human cells, and regulated primate foamy virus type I (PFV-1) proliferation. Several mammalian viruses, including the herpesvirus family, such as Epstein-Barr virus (EBV), simian virus 40 (SV40), and Kaposi sarcoma-associated virus, have been found to code miRNAs (Pfeffer et al, , 2005Cai et al, 2005;Grey et al, 2005;Omoto and Fujii, 2005;Sullivan et al, 2005;Sullivan and Ganem, 2005a,b;Cai and Cullen, 2006;Jiang et al, 2006;Schuetz and Sarnow, 2006;Simon-Mateo and Garcia, 2006). Although the function of these coding miRNAs is still unknown, it may play a role in human disease development.…”
Section: Functions Of Micrornas In Animalsmentioning
confidence: 99%